The Effect of Morphological Awareness on Lexical Knowledge of Grade 7 Learners - Cabe, Alphil Christian; Isla, Norman Ralph B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
There have been studies attesting that morphological awareness could develop vocabulary; yet several articles argued that lexis is a more encompassing linguistic feature than vocabulary. Hence, this quasi-experimental study sought to investigate the effect of morphological awareness on lexical knowledge of Grade 7 learners in a government high school in City of Koronadal, South Cotabato. Two groups with 45 learners each were selected to form the control and experimental groups. The two groups had a satisfactory performance and showed no significant difference in their scores in the beginning of the study. Then, they received the same 12-hour intervention within two weeks. Through dependent samples t-test, the result indicated that there was a significant difference between their scores in the beginning and end of the intervention. Moreover, through independent samples t-test, the result indicated that there was a significant difference between the scores of control and experimental groups in the end of the intervention. The experimental group that received the treatment showed a higher level of lexical knowledge than the control group. Thus, the study concluded that morphological awareness was effective on developing lexical knowledge among Grade 7 learners.